Definition of terms and presentation of processes regarding the collection, recycling and capitalization of waste packaging from agricultural activities - Alin-Angelin Iorga (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
Packaging, packaging waste and agriculture are separate, distinct concepts for Romania in 2015; they seem to have nothing in common. By bringing these words together and thoroughly studying the areas which they represent, we noticed that they are the starting point in defining a new concept: "Agriculture Waste Packaging". This concept is in fact a new issue which Romania will have to face and can bring great harm to the country's natural heritage no later than in 2020.
Keywords: 330; packaging; packaging waste; packaging waste from agriculture